The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/mcb.22.19.6779-6787.2002
|View full text |Cite
|
Sign up to set email alerts
|

The SWI/SNF Chromatin-Remodeling Factor Stimulates Repair by Human Excision Nuclease in the Mononucleosome Core Particle

Abstract: To investigate the role of chromatin remodeling in nucleotide excision repair, we prepared mononucleosomes with a 200-bp duplex containing an acetylaminofluorene-guanine (AAF-G) adduct at a single site. DNase I footprinting revealed a well-phased nucleosome structure with the AAF-G adduct near the center of twofold symmetry of the nucleosome core. This mononucleosome substrate was used to examine the effect of the SWI/SNF remodeling complex on the activity of human excision nuclease reconstituted from six puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
132
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 56 publications
(93 reference statements)
4
132
0
Order By: Relevance
“…In vitro, the ATP-dependent chromatin remodeler ACF can facilitate the dual incision step of NER within the linker DNA of a dinucleosomal template, although not within the nucleosome core particle [9]. Similarly, the ATP dependent chromatin remodeler SWI/ SNF can facilitate repair within the nucleosome core particle by a reconstituted human NER system [57]. It is possible that the addition of histone chaperones may further increase the efficiency of NER in vitro by their ability to unpackage chromatin, but this has not yet been experimentally demonstrated.…”
Section: Chromatin Assembly During Excision Repairmentioning
confidence: 99%
“…In vitro, the ATP-dependent chromatin remodeler ACF can facilitate the dual incision step of NER within the linker DNA of a dinucleosomal template, although not within the nucleosome core particle [9]. Similarly, the ATP dependent chromatin remodeler SWI/ SNF can facilitate repair within the nucleosome core particle by a reconstituted human NER system [57]. It is possible that the addition of histone chaperones may further increase the efficiency of NER in vitro by their ability to unpackage chromatin, but this has not yet been experimentally demonstrated.…”
Section: Chromatin Assembly During Excision Repairmentioning
confidence: 99%
“…BAF47-deficient cells are hypersensitive to genotoxic stress (Klochendler-Yeivin et al, 2006), and re-expression of BRG1 in BRG1-deficient SW13 cells renders the cells resistant to ultravioletinduced DNA damage (Gong et al, 2008). SWI/SNF facilitates the repair of cyclobutane pyrimidine dimers (Gaillard et al, 2003) and acetylaminofluorene-guanine adducts (Hara and Sancar, 2002) in a nucleosomal context. Studies carried out in vivo indicate that SWI/ SNF is recruited to double-strand break sites (Chai et al, 2005), and the inactivation of the SWI/SNF complex results in inefficient DNA double-strand break repair in vivo (Park et al, 2006).…”
mentioning
confidence: 99%
“…Biochemical studies showed that nucleosome assembly on in vitro NER substrate was severely inhibitory to the dual incision in either cell-extractbased or reconstituted assays (16)(17)(18). This inhibition can be mitigated by the presence of the yeast SWI/SNF complex in the reaction (19,20), which suggests that chromatin reconfiguration is likely a necessary step preceding NER. However, which ATPdependent remodeling complex or complexes provide the principal in vivo remodeling activity in aiding NER is unknown.…”
mentioning
confidence: 99%